PENINGKATAN BRAND LOYALTY MELALUI BRAND IMAGE, BRAND LOVE, DAN CUSTOMER SATISFACTION - Putri Yana Sari; Ken Sudarti (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2016)
The development of business technology that continues to grow in recent years more and more tight, because this business is the demands of the public about the importance of communication. Communication is a human need is very important and needed in the life of society to find and get information from or to other people. The need to get information on the rise as the development of the times. One of commmunication is needed to communicate wherever they are is handphone.The purpose of this study was to analisys the influence of brand image on brand love, the influence of brand image on customer satisfaction. The influence of brand image on brand loyalty. The influence of brand love on brand loyalty and the influence customer satisfaction on brand loyalty. This study uses UNISSULA student populations that uses Nokia mobile phones, while samples in this study were 100 respondent. The sampling technique with purposive sampling and data analisys methode uses is path analisys.The result of this research is : Brand image positive and significant impact on brand love, this means that if the brand image incrases, the love of the brand will also increases. Brand image positive and significant impact on customer satisfaction, this means that if the brand image incrases, customer satisfaction will also increases. Brand image positive significant impact on brand loyalty, this means if the brand image increases, brand loyalty also increases. Brand love positive significant impact on brand loyaly, this means that if the brand love increases, brand loyalty also increases. And customer satisfaction positive significant impact on brand loyalty, this means that customer satisfaction increases, brand loyalty also increases.